Low-hardness sponge rubber compound mixing process
By using carbon black and oil softener in low-hardness sponge glue and multiple stacking treatments, combined with heating static adsorption, dynamic stirring and cooling processes, and finally kneading in a dense mixer, the insufficient dispersion of carbon black is solved. The problem has improved the surface quality and production efficiency of sponge rubber strips.
Patent Information
- Application Number
- CN202411745502.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
AI Technical Summary
The carbon black dispersion in low-hardness sponge glue is insufficient, resulting in insufficient shear force during mixing and poor dispersion of carbon black, which affects the surface smoothness and crust effect of the sponge glue strips, and increases waste and scrap rate.
By infiltrating the carbon black and oil softener, static adsorption and repeated layering treatment, then heating and static adsorption, dynamic stirring and cooling, and finally kneading in a dense mixer to ensure that the carbon black and oil softener are fully adsorbed and dispersed.
It effectively solves the problem of insufficient dispersion of carbon black, improves the shear force of the mixed glue, ensures uniform distribution of carbon black, improves the surface smoothness and crust effect of the sponge rubber strips, and reduces waste and scrap rate.
Smart Images

Figure CN119431830A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of rubber manufacturing, in particular to a mixing process for low-hardness sponge rubber compound. Background Art
[0002] In order to have a better sponge foaming effect, the plasticity or Mooney and maturity of the rubber mix are critical control indicators. Precisely because a lower Mooney viscosity or higher plasticity is a necessary prerequisite for ensuring the foaming of the sponge rubber, the Mooney viscosity of the rubber mixes of various sponge rubber materials is relatively low, and the hardness is relatively low, which will bring a new mixing problem and difficulty. Because the rubber hardness is low and the Mooney is low, the shear force of the rubber mix during mixing is relatively low, and it is easy for the carbon black in the rubber mix to be poorly dispersed and unable to disperse. The rubber mix is wrapped with the undispersed carbon black. Even after many refining and thinning in the mixing mill, the effect is not very ideal. In the subsequent extrusion of the vulcanized sponge rubber strip, it is easy for carbon black particles to precipitate on the surface of the sponge rubber strip, there are more impurity particles on the surface of the rubber strip, the surface of the rubber strip is not well crusted, the surface is not smooth, there are more waste and defective products, and the scrap volume is relatively large.
[0003] The carbon black of low-hardness sponge rubber is not easy to disperse and is easy to clump. Particles are easily generated during extrusion. The surface crust is not good and is not smooth. The defective rate is high and the scrap volume is large. These are common problems and technical difficulties in the sponge extrusion sealing strip industry. Because too much oil softener is added at one time, the carbon black cannot absorb the oil softener in a short time, resulting in a low Mooney value of the overall viscosity of the mixed rubber and a low shear force. The wet granulated carbon black cannot be sheared and dispersed, resulting in the problem of poor carbon black dispersion.
[0004] How to fully disperse carbon black during the mixing process is a problem that needs to be solved. Summary of the invention
[0005] The purpose of the present invention is to provide a low-hardness sponge rubber mixing process to solve the problem of insufficient dispersion of carbon black.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The present invention provides a low-hardness sponge rubber mixing process, comprising the following steps:
[0008] S1. Preparation work 1: impregnating appropriate carbon black and oil softener to obtain a first intermediate;
[0009] S2. Preparation work 2, including:
[0010] S21, adding a proper amount of carbon black and spraying a proper amount of oil softener onto the carbon black;
[0011] S22, static adsorption for 5-10 minutes;
[0012] S23, repeat S21 and S22 multiple times to obtain a second intermediate;
[0013] S3, mixing the first intermediate and the second intermediate to obtain a mixture, heating and statically adsorbing for 1-2 hours at a temperature of 60-80°C;
[0014] S4, heating and dynamic stirring for 10-20 minutes, maintaining the temperature at 60-80°C;
[0015] S5. Static cooling for 1-2 hours at 20-40°C, weighing according to the formula;
[0016] S6. Mixing is performed in an internal mixer.
[0017] Optionally, in S4, the dynamic stirring speed is 60-100 rpm, and the speed is first slow and then fast.
[0018] Optionally, in S6, the mixing capacity of the internal mixer is increased by 10-20%.
[0019] Optionally, in S6, the internal mixer has a rotor, the mixture temperature is below 120°C, and the rotor speed is 45-55 rpm.
[0020] Furthermore, in S6, an upper push bolt is provided inside the internal mixer, and the internal mixer mixture is continuously heated to a temperature above 120° C., and the internal mixer produces the rubber compound. Each time the upper push bolt turns the rubber compound, the rotor speed is gradually reduced, and finally reduced to 35-40 rpm.
[0021] Furthermore, in S6, the internal mixer mixture is further heated to a temperature between 165 and 175°C for debinding.
[0022] Furthermore, in S6, the pressure of the upper push pin is increased by 10-30%.
[0023] Optionally, in S6, raw rubber is added to the internal mixer in advance, the raw rubber is plasticated for 60-90 seconds, and then added to the internal mixer for mixing.
[0024] Further, in S6, the glue is baked at a temperature of 80-100° C. for 2-4 hours.
[0025] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0026] The invention discloses a low-hardness sponge rubber mixing process. The carbon black and the oil softener are fully infiltrated and then soaked. The carbon black and the oil softener are stacked for multiple times. The infiltrated and stacked carbon black and the oil softener are then mixed so that the carbon black in the mixture fully absorbs the oil softener. The mixture is fully stirred and cooled to obtain a mixture. In this process, the carbon black is fully broken up and evenly distributed, thereby solving the problem of insufficient dispersion of the carbon black. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-restrictive manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale.
[0028] In the attached figure:
[0029] Figure 1 The present invention is a flow chart of a mixing process of a low-hardness sponge rubber compound according to a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0032] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0033] The present invention discloses a low-hardness sponge rubber mixing process, wherein the carbon black used is a mixture of one or more selected from carbon black N550, carbon black N660, and carbon black N774; the oil softener selected is a mixture of one or more selected from paraffin oil and naphthenic oil, comprising the following steps:
[0034] S1. Preparation work 1: soaking an appropriate amount of carbon black and oil softener, soaking the carbon black and oil softener thoroughly to obtain the first intermediate.
[0035] S2. Preparation work 2, including:
[0036] S21. According to the specifications of the stirring kettle, 20-30% of carbon black is put into the stirring kettle and evenly spread on the bottom of the kettle, and then 20-30% of oil softener is atomized and sprayed onto the surface of the carbon black through a high-pressure oil pump.
[0037] S22, statically adsorbing the materials in step S21, that is, the carbon black and the oil softener in the stirring kettle for 5-10 minutes.
[0038] S23, repeat S21 and S22 multiple times, at least 3 to 5 times, to obtain a second intermediate, a layer of oil softener is sprinkled on a layer of carbon black, to form multiple layers of oil softener and multiple layers of carbon black, and preparation work one and preparation work two are carried out simultaneously.
[0039] S3, mixing the first intermediate and the second intermediate to obtain a mixture, heating at 60-80°C and statically adsorbing for 1-2 hours, heating the stirring kettle at 60-80°C, so that the carbon black and the oil softener further adsorb to each other.
[0040] S4. After the static adsorption is completed, heat at 60-80℃ and start dynamic stirring, stir for 10-20 minutes, and maintain the temperature at 60-80℃. During this process, the carbon black and the oil softener are fully mixed, the carbon black is sufficiently dispersed, and the carbon black is broken up.
[0041] Then, the mixture of carbon black and oil softener is allowed to stand and cool for 1-2 hours. The mixture of carbon black and oil softener after being fully stirred is cooled in a static state. After cooling to 20-40°C, the mixture of carbon black and oil softener is divided into multiple portions according to the equipment specifications of the internal mixer.
[0042] S6. Mixing is performed in an internal mixer. The carbon black on the rubber mixed in the internal mixer is evenly dispersed.
[0043] In S4, the dynamic stirring speed is 60-100 rpm, and the speed is slow at first and then fast, so that the carbon black and the oil softener are thoroughly stirred, the carbon black particles are broken up and fully mixed with the oil softener. During the static adsorption and stirring process, the stirring kettle is in a heated state.
[0044] In S6, the mixing capacity of the internal mixer is increased by 10-20%, which is an increase of 10-20% on the mixing capacity of the existing internal mixer, so as to increase the shear force of the internal mixer on the rubber material, so that the carbon black oil softener can be better dispersed after stirring.
[0045] In S6, the internal mixer has a rotor, the mixture temperature is below 120°C, the rotor speed is 45-55 rpm, the rotor speed is 45-55 rpm at the beginning, and the rotor speed decreases as the temperature increases.
[0046] In S6, the internal mixer is provided with an upper push pin, which continues to heat the internal mixer mixture until the temperature reaches above 120°C, and the internal mixer produces the rubber compound. Each time the upper push pin turns the rubber compound, the rotor speed is gradually reduced, and finally drops to 35-40 rpm, at which time the rubber compound has been turned over.
[0047] In S6, the internal mixer mixture is continuously heated to a temperature between 165 and 175°C for debonding. The debonding at this time is primary debonding.
[0048] In S6, the pressure of the upper push pin is increased by 10-30%. The pressure of the upper push pin is increased by 10-30% compared with the existing one, so as to increase the shear force of the internal mixer on the rubber material, so that the carbon black and oil softener can be better dispersed after stirring.
[0049] In S6, raw rubber is added to the internal mixer in advance. The raw rubber used in this process is mainly EPDM rubber, with brands such as EP9950C and SK7486. The raw rubber is plasticized for 60-90 seconds and then added to the internal mixer for mixing. The raw rubber is added to the mixture formed by carbon black and oil softener to ensure that the overall viscosity of the carbon black is relatively low after adding a large amount of softener.
[0050] In S6, the rubber is baked at a temperature of 80-100°C for 2-4 hours to ensure that the Mooney viscosity of the raw rubber is reduced and there is no greater shear force on the raw rubber. This prevents the raw rubber from being broken up and dispersed after discharge. In the mixed rubber of low-hardness sponge rubber, it is not only the carbon black that is not broken up and dispersed poorly, but sometimes the raw rubber with high Mooney may also be broken up and dispersed poorly. Therefore, the high Mooney raw rubber should be baked in advance.
[0051] The present invention is further described below through specific examples and comparative examples. The feeding data of carbon black and oil softener used in the examples of the present invention are shown in the following table: It should be noted that the carbon black brand and oil softener selected in Examples 1 to Comparative Examples 6 of the present invention are the same, but the present invention limits the use scope of carbon black and oil softener, so any brand of carbon black or a mixture of carbon blacks of different brands within the scope defined by the present invention and any combination of oil softener or oil softener mixture should be covered within the protection scope of the present invention.
[0052] Table 1
[0053]
[0054] Table 2
[0055]
[0056]
[0057] After comparative verification and analysis, we found that the pre-dispersion effect of carbon black and oil softener in Example 1, which was statically adsorbed at 70°C for 1.5 hours, dynamically stirred for 15 minutes, and statically cooled at 30°C for 1.5 hours, was the best. The dispersion grade and carbon black dispersion were also better than those in other embodiments and comparative examples. The batch differences were relatively small and stable.
[0058] Further increasing the temperature, adsorption, stirring and cooling time will not significantly improve the dispersion grade and degree of the mixed rubber. The overall trend is toward a stable state. Considering production costs and production efficiency, there is no need to increase time and temperature.
[0059] However, under the conditions of static adsorption and stirring at a temperature below 60°C and a time of 1 hour and 10 minutes, the dispersion grade and dispersion degree of the mixed rubber are relatively low and cannot reach the desired control level. Therefore, among the embodiments and comparative examples, Example 1 is the most suitable. In the other embodiments and comparative examples, either the desired dispersion grade and dispersion degree cannot be achieved, or time and energy are wasted, which is not economical and inefficient. Therefore, after comparing the different temperature times in the embodiments and comparative examples and verifying the three process steps of static adsorption, dynamic stirring and static cooling, it is found that too short a time and too low a temperature cannot achieve the desired dispersion level, while too long a time and too high a temperature do not have a significant effect or space on improving the dispersion grade and dispersion degree. Therefore, after verification and comparative analysis of the process steps and time and temperature, Example 1 is a process that is more suitable for factory operation.
[0060] Table 3
[0061]
[0062]
[0063] The above is just a conventional formula. In actual use, the three brands of carbon black can be mixed and used, and paraffin oil and cyclohexane oil can also be mixed and used.
[0064] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A low hardness sponge rubber mixing process, characterized in that: The steps include: S1. Preparation work 1: impregnating an appropriate amount of carbon black and an oil softener to obtain a first intermediate; S2. Preparation work 2, including: S21, adding a proper amount of carbon black and spraying a proper amount of oil softener onto the carbon black; S22, static adsorption for 5-10 minutes; S23, repeat S21 and S22 multiple times to obtain a second intermediate; S3, mixing the first intermediate and the second intermediate to obtain a mixture, heating and statically adsorbing for 1-2 hours at a temperature of 60-80°C; S4, heating and dynamic stirring for 10-20 minutes, maintaining the temperature at 60-80°C; S5. Static cooling for 1-2 hours at 20-40°C, weighing according to the formula; S6. Mixing is performed in an internal mixer.
2. The low hardness sponge rubber compound mixing process according to claim 1, characterized in that: In S4, the dynamic stirring speed is 60-100 rpm, and the speed is slow at first and then fast.
3. The low hardness sponge rubber compound mixing process according to claim 1, characterized in that: In S6, the mixing capacity of the internal mixer is increased by 10-20%.
4. The low-hardness sponge rubber compound mixing process according to claim 1, characterized in that: In S6, the internal mixer has a rotor, the mixture temperature is below 120°C, and the rotor speed is 45-55 rpm.
5. The low-hardness sponge rubber compound mixing process according to claim 4, characterized in that: In S6, the internal mixer is provided with an upper push pin, which continues to heat the internal mixer mixture until the temperature reaches above 120°C, and the internal mixer produces the rubber compound. Each time the upper push pin turns the rubber compound, the rotor speed is gradually reduced, and finally reduced to 35-40 rpm.
6. The low-hardness sponge rubber mixing process according to claim 5, characterized in that: In S6, the internal mixer mixture is further heated to a temperature between 165 and 175°C for debinding.
7. The low-hardness sponge rubber mixing process according to claim 5, characterized in that: In S6, the pressure of the top bolt should be increased by 10-30%.
8. The low-hardness sponge rubber compound mixing process according to claim 1, characterized in that: In S6, raw rubber is added to the internal mixer in advance, and the raw rubber is plasticated for 60-90 seconds, and then added to the internal mixer for mixing.
9. The low-hardness sponge rubber compound mixing process according to claim 8, characterized in that: In S6, the glue is baked at a temperature of 80-100° C. for 2-4 hours.
Citation Information
Patent Citations
Block copolymer hot melt adhesive composition and method of filling a cavity
EP0009950A1